The Relationship between Waiting Time and Patient Satisfaction in Responsiveness and Accuracy at the Emergency Room of Pekajangan - Ahmad Samsudin; Trina Kurniawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Waiting time is measured when the patient arrives in the ER until he is transferred to the inpatient wards. Crowding is a problem that often occurs in the ER, which can prolong waiting times, thus affecting the responsiveness and accuracy of emergency services to patients. This study aims to determine the relationship between waiting time and patient satisfaction regarding speed accuracy of service at the emergency department of Pekajangan Hospital. This study involved 150 respondens of ER patient. Accidental sampling technique was used. A descriptive correlative study was used. Data were analysed by using the chi-square test. The result of this study showed that there is no relationship between waiting time and patient satisfaction in terms of responsiveness and accuracy of services in the ER (p-value = 0.820). Similar result was found in the aspect of responsiveness and accuracy of registration, radiology, laboratory and pharmacy services (p-value <0,05). The result showed that there no relationship between waiting time and patient satisfaction in terms of responsiveness and accuracy of service in the emergency department.